Forecasting Volcanic Eruptions: Beyond the Failure Forecast Method - Kilburn, Christopher R. J. (Frontiers in Earth Science, 2018)
Volcano-tectonic seismicity and ground movement are the most reliable precursors to eruptions after extended intervals of repose, as well as to flank eruptions from frequently-active volcanoes. Their behavior is consistent with elastic-brittle failure of the crust before a new pathway is opened to allow magma ascent. A modified physical model shows that precursory time series are governed by a parent relation between faulting and elastic deformation in extension, subject to independent constraints on the rate of crustal loading with time. The results yield deterministic criteria that can be incorporated into existing operational procedures for evaluating the probability of crustal failure and, hence, levels of alert during an emergency. They also suggest that the popular Failure Forecasting Method for forecasting eruptions is a particular form of the parent elastic-brittle model, and that magma transport and crustal fracturing during unrest tend towards conditions for minimizing rates of energy loss.